The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s11270-023-06142-w
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research on Municipal Sludge as Soil Fertilizer in China: a Review

Abstract: Due to the annual increase in wastewater treatment in most Chinese cities, a major environmental issue has arisen: safe treatment, disposal, and recycling of municipal sludge. Municipal sludge has a high content of carbon and essential nutrients for plant growth; hence, it has gained interest among researchers as a soil fertilizer. This study discusses the potential usage of municipal sludge as soil fertilizer (indicators include nitrogen (N), phosphorus (P), and trace elements) along with its shortcomings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 80 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…In comparison to the findings of previous reports, these results demonstrate a significantly improved performance in terms of CPX removal time. Ahmed et al 44 reported that it took 60 min to remove 75% of the CPX onto ZVI@ biochars, whereas the ZVNi@AC achieved the same level of removal within a mere 5 min.…”
Section: Characterizationmentioning
confidence: 99%
“…In comparison to the findings of previous reports, these results demonstrate a significantly improved performance in terms of CPX removal time. Ahmed et al 44 reported that it took 60 min to remove 75% of the CPX onto ZVI@ biochars, whereas the ZVNi@AC achieved the same level of removal within a mere 5 min.…”
Section: Characterizationmentioning
confidence: 99%
“…was not detected in any case. DS was produced exclusively on the basis of food wastes, which are usually not as rich a source of enteropathogens as municipal waste and human and animal manure (Manyi-Loh et al 2016; Zhang et al 2023). However, plant material can also be a source of this type of microorganisms due to the contact with soil (Patel et al 2014).…”
Section: Microbial Analysismentioning
confidence: 99%
“…22,23 CS molecular chains penetrate the interlayer of columnar bent and attach to its surface, strengthening its adsorption capacity. Chong Huang et al 24 looked into the adsorption effect of acid-chitosanbentonite composite on Cr 6+ in solution. Their ndings suggest that the maximum adsorption capacity may be 111.47 mg g −1 and that spontaneous and endothermic monolayer chemical adsorption is the adsorption mechanism.…”
Section: Introducementioning
confidence: 99%